Chemical Ecology of Capnodis tenebrionis (L.) (Coleoptera: Buprestidae): Behavioral and Biochemical Strategies for Intraspecific and Host Interactions - Bari, Giuseppe; Scala, Andrea; Garzone, Vita; Salvia, Rosanna; Yalcin, Cem; Vernile, Pasqua; Aresta, Antonella Maria; Facini, Osvaldo; Baraldi, Rita; Bufo, Sabino A.; Vogel, Heiko; de Lillo, Enrico; et al. (Frontiers in Physiology, 2019)
This study focuses on several aspects of communication strategies adopted by adults of the Mediterranean flat-headed root-borer Capnodis tenebrionis (Coleoptera: Buprestidae). Morphological studies on the structures involved in mate recognition and acceptance revealed the presence of porous areas in the pronota in both sexes. These areas were variable in shape and size, but proportionally larger in males. The presence of chaetic, basiconic, and coeloconic sensilla in the antennae of both males and females was verified. Bioassays revealed stereotyped rituals in males and the involvement of female pronotal secretions in mate recognition and acceptance. During the mating assays, the female’s pronotum was covered by a biologically inert polymeric resin (DenFilTM), which prevented males from detecting the secretions and from completing the copulation ritual. The use of the resin allowed for the collection of chemical compounds. GC-MS analysis of the resin suggested it may be used to retain compounds from insect body surfaces and revealed sex-specific chemical profiles in the cuticles. Since adult C. tenebrionis may use volatile organic compounds (VOCs) emitted from leaves or shoots, the VOC emission profiles of apricot trees were characterized. Several volatiles related to plant-insect interactions involving fruit tree species of the Rosaceae family and buprestid beetles were identified. To improve understanding of how VOCs are perceived, candidate soluble olfactory proteins involved in chemoreception (odorant-binding proteins and chemosensory proteins) were identified using tissue and sex-specific RNA-seq data. The implications for chemical identification, physiological and ecological functions in intraspecific communication and insect–host interactions are discussed and potential applications for monitoring presented.